(untitled) (Semiárida, 2021)
Bread wheat cultivation is very important for the dry subhumid region, but its yield shows interannual instability. The objective of this work was to analyze in this region the effect of genetic improvement on yield stability and yield components in cultivars prior (old) and subsequent (modern) to the incorporation of dwarfism genes. The trials were carried out in Santa Rosa, La Pampa, Argentina (36o 32’ 49” S; 64º 18’ 20” W) for 7 years, with 4 genotypes and 2 soil fertility conditions (0 and 100 kg.ha 1 of urea). The grain yield was higher in modern cultivars than to the old ones, even in negative environmental indices; however, this difference did not cause a decrease in stability; and the response to nitrogen was similar in modern and old cultivars. The number of grains.m2 explained in a greater proportion the variation in yield than the weight of a thousand grains; and within the first component it was observed that the number of grains per spike increased in a greater proportion than the number of spikes.m2. The aerial biomass increased in the modern cultivars with respect to the old ones, but in less proportion than the harvest index and the plant height.